Magic Tree House #12 : Polar Bears Past Bedtime - Mary Pope Osborne (Random House USA Children's Books New York, 1998)
The Magic Tree House transportss Jack and Annie to the freezing Arctic. There, they must solve the final riddle to become master librarians. But it's not going to be easy--especially when they have cracking ice, a seal hunter, and a prodigious polar bear to deal with. Will they be able to solve the riddle before they get iced themselves?
Keywords: Historical Fiction + Fantasy -- Historical Fiction + Fantasy